Case reports High-dose-rate brachytherapy – a novel treatment approach for primary clear cell adenocarcinoma of male urethra - Lewis, Shirley; Pal, Mahendra; Bakshi, Ganesh; Ghadi, Yogesh G.; Menon, Santosh; Murthy, Vedang; Mahantshetty, Umesh (Journal of Contemporary Brachytherapy, 2015)
The incidence of male urethral cancer is rare with age preponderance of 50 to 60 years. The standard management approach is surgery. Here, we present a novel treatment approach for male urethral cancer. Thirty-six year old male, case of primary clear cell adenocarcinoma of urethra who refused surgery, underwent cystoscopic assisted intraluminal HDR brachytherapy. Patient received a dose of 36 Gy in 9 fractions (4 Gy per fraction) followed by a boost of 24 Gy in 6 fractions. At 11 months post treatment, disease is well controlled with no post treatment toxicity so far. Intraluminal brachytherapy seems to be an effective novel treatment for male urethral cancer.